SECOND ORDER NONLINEAR FUNCTIONAL RANDOM DIFFERENTIAL EQUATION - Bhosale, Meghana Kashinath (Journal of Global Research in Mathematical Archives(JGRMA), 2014)
In this paper we prove the existence of the solution for the second order nonlinear functional random differential equation under the Carathéodory condition, compactness and monotonic condition. 2000 Mathematics Subject Classification: 47H10, 34F05. Keywords and phrases: Functional Random differential equation, Existence theorem, Carathéodory condition, Random Fixed Point TheoremÂ Â etc.